Positive and Negative Regulation of the Transforming Growth Factor β/Activin Target Gene goosecoid by the TFII-I Family of Transcription Factors - Ku, Manching (American Society for Microbiology, 2005)
Goosecoid (Gsc) is a homeodomain-containing transcription factor present in a wide variety of vertebrate species and known to regulate formation and patterning of embryos. Here we show that in embryonic carcinoma P19 cells, the transcription factor TFII-I forms a complex with Smad2 upon transforming growth factor β (TGFβ)/activin stimulation, is recruited to the distal element (DE) of the Gsc promoter, and activates Gsc transcription. Downregulation of endogenous TFII-I by small inhibitory RNA in P19 cells abolishes the TGFβ-mediated induction of Gsc. Similarly, Xenopus embryos with endogenous TFII-I expression downregulated by injection of TFII-I-specific antisense oligonucleotides exhibit decreased Gsc expression. Unlike TFII-I, the related factor BEN (binding factor for early enhancer) is constitutively recruited to the distal element in the absence of TGFβ/activin signaling and is replaced by the TFII-I/Smad2 complex upon TGFβ/activin stimulation. Overexpression of BEN in P19 cells represses the TGFβ-mediated transcriptional activation of Gsc. These results suggest a model in which TFII-I family proteins have opposing effects in the regulation of the Gsc gene in response to a TGFβ/activin signal.